TANGGAP PETANI GUREM DI DESA MISKIN KABUPATEN TEMANGGUNG TERHADAP INOVASI TEKNOLOGI PERTANJAN - Abdul Choliq; Agus Hermawan; Forita D. A (JURNAL LITBANG PROVINSI JAWA TENGAH, 2006)
During new order period, priority was given to the hi-tech industry sector and less favorable to the agricultural sector. Many researchers pointed out that.the previous policy as the main cause of the current big numbers of peasant farmers.Poor farmers responsed to the innovation differently, Tbe response was affected by several factors. To find out the response, deeper assessment was carried out from August to October 2004 in Ternanggung District. Peasant farmers, coming from the medium and high land, were interviewed using structural questionnaire. Aside of primary data, secondary data was gathered from related institutions. Research showed that high land peasant farmers were more passive than medium land farmers, High land farmers had less ability on capital improvement, risk-averse to the new program, discouraged to change fanning practices, and their expertise improvement effortwas less than those of medium land farmers. Factors affecting were low education attainment and less infrastructure supports (i.e. transportation.informauon, formal banking institution). Up to the end of the new order period, KUT!Kredit Usahatani (Farming Credit) was the only source of formal.credit for farmers, Along with the Banking regulation, KUT was changed to KKP/Kredit Ketahanan Pangan (Food Security Credit). However, the new scheme credit was not fully responded either.